Security‐constrained optimal scheduling and operation of island microgrids considering demand response and electric vehicles. (23rd October 2021) - Divani, Mohammad Yasin; Najafi, Mojtaba; Ghaedi, Amir; Gorginpour, Hamed
Abstract: As an independent unit, microgrid operator (MGO) should respond to the energy demand of customers with an optimal provision cost. Apart from the ability to guarantee the security of microgrid (MG) operation, the MGO should consider the greenhouse emission effects as well. This paper investigates a novel energy management system for an islanded MG. In the proposed strategy, two efficient methodologies are used to maximize the profit and security of the MG: (a) the optimal operation of electric vehicles (EVs) in vehicle‐to‐grid (V2G) mode and (b) the use of demand response (DR) program. Besides, a hierarchical control structure is proposed to manage frequency and voltage uncertainties in a permissible range. Improving the reliability of the MG is another goal of the proposed strategy, which is pursued by the studied controlling framework. The proposed approach is evaluated through a set of simulation and GAMS tests. Results indicate that the frequency deviation of the MG is damped through the proposed management strategy and place the spotlight on the effectiveness of the approach. Abstract : In this paper, the multi‐objective coordinated operation of MG resources based on economic and security objectives is presented. Unlike the previous works, the proposed model considers both operation cost and security of MG. In the proposed scheme, an MG central controller (MGCC) is designed as the tertiary control level. This control level, which is the main part of the proposed model, integrates other segments of the MG and performs coordinated economic‐security scheduling and operation of an islanded MG based on stochastic programming. In the proposed model, the scheduling of dispatchable units not only secures MG frequency and voltage but also guarantees the maximum expected profit from the viewpoint of the MG operator. Due to the dependency of the RESs on weather conditions, the optimal operation of MG has been performed under weather uncertainty. In addition to DG units, the proposed model also incorporates electrical loads to maximize profits. For responsive loads, it is possible to analyze the effects of customers' participation in the DR program on the economic and security of islanded MG. Most of the previous works utilized DC‐OPF in their optimization model, resulting in neglecting reactive power and its significant effect on node voltages. In this paper, however, the frequency and voltage deviations are accurately calculated through AC security‐constraint OPF and are compensated at the secondary control level.